Aerobic stability of whole plant corn silage inoculated with a bacterial inoculant in three maturity stages - Camarasa, Jonatan Nicolás; Auil, M.; Barletta, Pablo Fernando; Bereterbide, L. (Ediciones INTA, 2021)
Maturity stage (MS) at harvesting is the most important factor that determines the nutritive value and productivity of corn silage. Once opened, the silage for supplyis exposed to oxygen deterioration due to aerobic microbial activity, which could negatively influence the quantity and quality of silage. There are bacterial inoculants containing microorganisms which improve the process of fermentation and the aerobic stability of silage. The aim was to evaluate the effect on aerobic stability produced by a bacterial inoculant in whole plant corn silage at different maturity stages (MS). The experimental design was factorial (n=3). The factors were: inoculated and state of maturity; the first with two levels: control and inoculated and the second with three levels: 25, 35 and 45% MS. The data were analyzed by ANOVA and the comparison of means by the Tukey test (p˂0.05). Maize crop was harvested: 25, 35 and 45% dry matter (DM). Chopped material was ensiled in 20 L buckets (six silos/MS), three of them were Inoculated (I) and three were not Control. The interactions between I*MS were not significant (P>0.05) for all variables. To the evaluated variables, there was no difference (P>0.05) among Inoculated vs. Control treatments. There was a difference (P<0.05) between MS, where 25% DM had higher water-soluble carbohydrates and acetic acid, which allowed greater aerobic stability than with 35 and 45% DM. DM losses with 45% DM treatment had the highest (P<0.05) loss compared to 25 and 35% DM. Results suggested there was no effect of bacterial inoculation but there were effect maturity stages on the aerobic stability of silage. As the harvest is delayed the silage has lower aerobic stability.